Every nursing support matters: Mothers of hospitalised preterm newborns - Yusrita Zolkefli (Belitung Raya Foundation, Indonesia, 2022)
Nursing support for mothers whose newborns are admitted to the neonatal intensive care unit (NICU) has been a subject of interest in nursing practice. The article by Ong et al. acknowledges the salient role of nurses in supporting mothers in the neonatal intensive care unit. While the study suggested a moderate quality of life among mothers, the authors emphasised the necessity for hospital management to provide tangible and structured strategies to reduce maternal stress. The paper describes some existing nursing support programs to illustrate the approaches.